Comparative study of Profitability and Liquidity analysis of Islamic Banks in Bangladesh - Fatema, Nazneen; Ibrahim, Abdullah Mohammed (Global Disclosure of Economics and Business, 2013)
In this depressed world financial scenario, Islamic banking has emerged as a strong alternate financial system. Its growth is not restricted to the Muslim societies but Islamic financial products are also gaining popularity among non-Muslim countries. The objective of this paper is to scrutinize and compare the liquidity and profitability performances of five Islamic banks in Bangladesh in between the period 2005 and 2011. In order to scan the performances, this study highlights on different standards of liquidity and profitability measurements logical to Islamic philosophy; such as liquidity and profitability ratios, liquidity reserves by the banks, net liquidity gap, profit creation from different sectors of the banks, etc. Multiple correlations among liquidity and profitability ratios are shown here. The results of all these measurements are quite apparent. In particular, among all the independent variables, at 90% confidence level only investment to total assets is found to be significantly affecting Return on Assets (a measurement of profitability ratio) for Islami Bank Bangladesh Ltd., Shahjalal Islami Bank Ltd. and EXIM Bank Ltd., whereas with Return on Equity for only Shahjalal Islami Bank Ltd. However, multicollinearity has been found to be a great issue when considering liquidity impact on profitability for Islami Bank Bangladesh Ltd., EXIM Bank Ltd. and Social Islami Bank Ltd. Overall P-values suggest that at 95% confidence level liquidity model proves significant on ROA for Islami Bank Bangladesh Ltd. and Social Islami Bank Ltd., while on ROE for Islami Bank Bangladesh Ltd. and Shahjalal Islami Bank Ltd. JEL Classification Code: G21; G30; M20